Preparation method of light-emitting device, light-emitting device and display device

The described method for preparing light-emitting diodes using oxygen ion irradiation to form a transition layer within the electroluminescent layer stack addresses the short lifespan issue, enhancing the longevity and efficiency of OLED and QLED devices.

CN119730645APending Publication Date: 2025-03-28TCL TECHNOLOGY GROUP CORPORATION +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311281916.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing methods for preparing OLED and QLED devices result in short-lived light-emitting diodes, necessitating an improvement in their lifespan.

Method used

A method involving the formation of a light-emitting diode structure with a pre-fabricated layer stack of an anode, an electroluminescent layer, and a cathode, where the electroluminescent layer includes inorganic semiconductor particles, and a conductive layer is created by oxygen ion irradiation to form a transition layer, enhancing the device's longevity.

Benefits of technology

This method effectively prolongs the lifespan of light-emitting diodes by promoting forward aging and improving their brightness and efficiency, while allowing for controlled thickness of the transition layer, thus enhancing overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119730645A_ABST
    Figure CN119730645A_ABST
Patent Text Reader

Abstract

The invention discloses a light-emitting device, a preparation method thereof and a display device. According to the preparation method of the light-emitting device, the conductive layer containing the metal elements is formed on the electronic function prefabricated layer, and then the conductive layer is subjected to oxygen ion irradiation, so that high-energy oxygen ions penetrate through the conductive layer and are injected into the interface between the conductive layer and the electronic function prefabricated layer; the high-energy oxygen ions injected to the interface can react with the inorganic semiconductor particles and the metal elements at the interface respectively, so that the area, close to the conductive layer, of the electronic function prefabricated layer and the conductive layer jointly form a transition layer, forward aging of the device is facilitated, and the performance such as the maximum brightness and the service life of the light-emitting device is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of light-emitting devices, and in particular to a method for preparing a light-emitting device, a light-emitting device and a display device. Background Art

[0002] Currently, the widely used light-emitting devices are organic light-emitting devices (OLED) and quantum dot light-emitting devices (QLED). OLED has become the mainstream technology in the field of display technology due to its excellent display performance such as self-luminescence, simple structure, ultra-thinness, fast response speed, wide viewing angle, low power consumption, and flexible display. QLED has the advantages of saturated color of emitted light, adjustable wavelength, low start-up voltage, good solution processability, easy fine control of quantum dots, and high quantum yield of photoluminescence and electroluminescence. In recent years, it has become a strong competitor of OLED.

[0003] The structure of traditional OLED and QLED devices generally includes an anode, a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, an electron injection layer and a cathode. Under the action of the electric field, the holes generated by the anode of the light-emitting device and the electrons generated by the cathode move and are injected into the hole transport layer and the electron transport layer respectively, and finally migrate to the light-emitting layer. When the two meet in the light-emitting layer, energy excitons are generated, thereby exciting the light-emitting molecules and finally producing visible light.

[0004] The life of the light-emitting device prepared by the existing method for preparing the light-emitting device is relatively short and needs to be further improved. Summary of the invention

[0005] In view of this, the present application provides a method for preparing a light-emitting device, aiming to improve the problem of short life of the light-emitting device prepared by the existing preparation method.

[0006] The embodiment of the present application is implemented as follows: a method for preparing a light-emitting device comprises the following steps:

[0007] Providing a light-emitting device prefabricated part, the light-emitting device prefabricated part comprising an anode, a light-emitting layer, and an electronic functional prefabricated layer stacked in sequence, wherein the electronic functional prefabricated layer comprises inorganic semiconductor particles;

[0008] Preparing a conductive layer on the electronic functional prefabricated layer, wherein the conductive layer contains a metal element;

[0009] The conductive layer is subjected to oxygen ion irradiation, so that the region of the electronic functional prefabricated layer close to the conductive layer and the conductive layer form a transition layer together, thereby obtaining a laminated electronic functional layer and a transition layer;

[0010] A cathode is prepared on the transition layer to obtain a light-emitting device.

[0011] Optionally, in some embodiments, the energy of the ion beam of the oxygen ion irradiation is 15-50 keV; and / or

[0012] The oxygen ion dose used in the oxygen ion irradiation is 1×10 12 ~1×10 16 ions / cm 2 .

[0013] Optionally, in some embodiments, the average thickness of the conductive layer is 5 to 30 nm; and / or

[0014] The average thickness of the transition layer is in the range of 10 to 50 nm.

[0015] Optionally, in some embodiments, the material of the conductive layer includes one or more of a metal element, a metal alloy and a doped metal oxide, wherein the metal element includes Ag, Al, Ni, Pt, Au, Ir, Cu, Mo, Ca, Mg and Ba; the metal alloy is composed of at least two metal elements in the metal element, optionally, the metal alloy includes silver-copper alloy, silver-nickel alloy, silver-magnesium alloy, silver-aluminum alloy, aluminum-magnesium alloy, aluminum-magnesium-zinc-copper alloy or gold-magnesium alloy; the doped metal oxide includes one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide, aluminum-doped magnesium oxide and cadmium-doped zinc oxide; and / or

[0016] The inorganic semiconductor particles include doped metal oxide particles, undoped metal oxide particles, one or more of IIB-VIA semiconductor materials, IIIA-VA semiconductor materials and IB-IIIA-VIA semiconductor materials. The material of the undoped metal oxide particles includes one or more of ZnO, TiO2, SnO2, ZrO2, and Ta2O5. The metal oxide in the doped metal oxide particles includes one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5, and Al2O3. The doping elements in the doped metal oxide particles include one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, and Ga. The IIB-VIA semiconductor materials include one or more of ZnS, ZnSe, and CdS. The IIIA-VA semiconductor materials include one or more of InP. The IB-IIIA-VIA semiconductor materials include one or more of CuInS and CuGaS.

[0017] Optionally, in some embodiments, the anode includes a doped metal oxide electrode, a composite electrode, a graphene electrode, a carbon nanotube electrode, a metal element electrode or an alloy electrode, the material of the doped metal oxide electrode includes one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide, aluminum-doped magnesium oxide, and cadmium-doped zinc oxide, and the composite electrode includes AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, Ca / Al, LiF / Ca, LiF / Al, BaF2 / Al, CsF / Al, CaCO3 / Al or BaF2 / Ca / Al, the material of the metal single substance electrode includes one or more of Ag, Ni, Pt, Au, Ir, Cu, Mo, Al, Ca, Mg and Ba, and the alloy electrode includes a silver-copper alloy electrode, a silver-nickel alloy electrode, a silver-magnesium alloy electrode, a silver-aluminum alloy electrode, an aluminum-magnesium alloy electrode, an aluminum-magnesium-zinc-copper alloy electrode or a gold-magnesium alloy electrode; and / or

[0018] The material of the light-emitting layer includes one or more of an organic light-emitting material and a quantum dot light-emitting material, and the organic light-emitting material includes one or more of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tri[2-(p-tolyl)pyridine iridium(III), 4,4',4"-tri(carbazole-9-yl)triphenylamine:tri[2-(p-tolyl)pyridine iridium, diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, thermally activated delayed materials, polymers containing covalent bonds of BN, hybrid localized charge transfer excited state materials, exciplex light-emitting materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives;The quantum dot luminescent material includes one or more of a single structure quantum dot, a core-shell structure quantum dot and a perovskite semiconductor material. The material of the single structure quantum dot, the core material of the core-shell structure quantum dot and the shell material of the core-shell structure quantum dot are independently selected from one or more of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds. The II-VI group compounds include CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, Zn STe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound includes SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, One or more of PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, the III-V group compound includes GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlN As, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, the I-III-VI group compound includes one or more of CuInS2, CuInSe2 and AgInS2; the perovskite semiconductor material includes a doped or undoped inorganic perovskite semiconductor or an organic-inorganic hybrid perovskite semiconductor, and the general structural formula of the inorganic perovskite semiconductor is AMX3, wherein A is Cs; + ions, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion, including Cl - Br - ,I - One or more of; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation, including CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion, including Cl - Br - ,I - One or more of;

[0019] The light-emitting device further comprises a hole transport layer between the anode and the light-emitting layer, wherein the material of the hole transport layer comprises 4,4'-N,N'-dicarbazolyl-biphenyl, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine), N,N'-bis(3 -methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(N-vinylcarbazole) and its derivatives, N,N'-di(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4- 4'-diamine, spiro NPB, poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene], poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline], 1,3-bis(carbazol-9-yl)benzene, polyaniline, polypyrrole, poly(p-)phenylene vinylene, aromatic tertiary amines, polynuclear aromatic tertiary amines , 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, doped graphene, undoped graphene, C60, doped or undoped NiO, doped or undoped MoO3, doped or undoped WO3, doped or undoped V2O5, doped or undoped P-type gallium nitride, doped or undoped CrO3, doped or undoped CuO; and / or

[0020] The light-emitting device also includes a hole injection layer located between the anode and the light-emitting layer, and the material of the hole injection layer includes one or more of 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, PEDOT, PEDOT:PSS, a derivative of PEDOT:PSS doped with s-MoO3, 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, tetracyanoquinodimethane, copper phthalocyanine, nickel oxide, molybdenum oxide, tungsten oxide, vanadium oxide, molybdenum sulfide, tungsten sulfide and copper oxide.

[0021] Accordingly, the embodiment of the present application also provides a light-emitting device, comprising an anode, a light-emitting layer, an electronic functional layer and a cathode stacked in sequence, and further comprising a transition layer, wherein the transition layer is located between the electronic functional layer and the cathode, and the transition layer comprises M'O x and M” n O y , wherein M' and M" are metal elements, x is any value from 0.1 to 1, y is any value from 0.1 to 1, and n is any value from 1 to 5.

[0022] Optionally, in some embodiments, M' is selected from one or more of Zn, Ti, Sn, Zr, Ta, Al, Mg, Li, Mn, Y, La, Cu, Ni, Ce, In, and Ga; and / or

[0023] The M" is selected from one or more of Ag, Al, Ni, Pt, Au, Ir, Cu, Mo, Ca, Mg, Ba, Sn, and Mg;

[0024] Optionally, the M'O x ZnO x , the M" n O y Ag2O y .

[0025] Optionally, in some embodiments, in the transition layer, along a side close to the electronic functional layer toward a side away from the electronic functional layer, the M′O x The value of x gradually increases, and M'O x The content of is distributed in a gradually decreasing gradient;

[0026] And / or, in the transition layer, M'O on the side close to the electronic functional layer x The content of M'O is higher than that of M'O on the side away from the electronic functional layer. x Content;

[0027] And / or, in the transition layer, along the side close to the cathode toward the side away from the cathode, the M"n O y The value of y in the equation decreases gradually, and M" n O y The content of is distributed in a gradually decreasing gradient;

[0028] And / or, in the transition layer, M" on the side close to the cathode n O y The content is higher than that of M" on the side away from the cathode n O y The content.

[0029] Optionally, in some embodiments, the average thickness of the transition layer is 10 to 50 nm, preferably 20 to 45 nm.

[0030] Correspondingly, an embodiment of the present application further provides a display device, which includes the above-mentioned light-emitting device.

[0031] In the preparation method of the light-emitting device described in the present application, a conductive layer containing metal elements is first formed on the electronic functional prefabricated layer, and then the conductive layer is irradiated with oxygen ions, so that high-energy oxygen ions pass through the conductive layer and are injected into the interface between the conductive layer and the electronic functional prefabricated layer. The high-energy oxygen ions injected into the interface can react with the inorganic semiconductor particles and the metal elements at the interface respectively, so that the area of ​​the electronic functional prefabricated layer close to the conductive layer and the conductive layer form a transition layer together, which is beneficial to the forward aging of the device and thus improves the life of the light-emitting device. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0033] Figure 1 is a flow chart of a method for preparing a light-emitting device provided in an embodiment of the present application;

[0034] Figure 2 It is a structural schematic diagram of a light-emitting device prefabricated part provided in an embodiment of the present application;

[0035] Figure 3 It is a schematic diagram of the structure of preparing an electronic functional prefabricated layer and a conductive layer on a light-emitting device prefabricated part provided in an embodiment of the present application;

[0036] Figure 4 is a schematic structural diagram of a light-emitting device provided in an embodiment of the present application;

[0037] Figure 5 is a schematic structural diagram of another light-emitting device provided in an embodiment of the present application;

[0038] Figure 6 It is a voltage-current density curve diagram of the light-emitting devices of Examples 1, 5, 8, 9, 11, 12 and Comparative Examples 1 to 6 of the present application;

[0039] Figure 7 It is a current density-external quantum efficiency curve diagram of the light-emitting devices of Examples 1, 5, 8, 9, 11, 12 of the present application and Comparative Examples 1 to 6.

[0040] Reference numerals:

[0041] Light-emitting device 100 ; anode 10 ; light-emitting layer 20 ; electronic functional layer 30 ; transition layer 40 ; cathode 50 , hole transport layer 60 ; hole injection layer 70 ; light-emitting device preform 200 ; electronic functional preform layer 101 ; conductive layer 102 . DETAILED DESCRIPTION

[0042] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0043] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.

[0044] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0045] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0046] In the present application, when a layer is formed "on" another layer, the so-called "on" is a broad concept, which may indicate that the formed another layer is adjacent to the certain layer, or may indicate that there are other spacing structural layers between the another layer and the certain layer. For example, when a second electrode is formed "on" the first carrier functional layer, the so-called "on" may indicate that the formed second electrode is adjacent to the first carrier functional layer, or may indicate that there are other spacing structural layers between the second electrode and the first carrier functional layer, such as a light-emitting layer.

[0047] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0048] After the preparation of the light-emitting device is completed, there will be forward aging, which is mainly caused by the reaction between the metal oxide in the electron transport layer and the metal in the cathode to form a transition oxide interface layer. Studies have found that the forward aging of the light-emitting device can effectively improve the device's photoelectric performance such as brightness, luminous efficiency and life. However, the natural forward aging has the problem of slow speed. Therefore, the prior art will perform post-annealing treatment on the light-emitting device after the preparation of the light-emitting device is completed to accelerate the forward aging of the light-emitting device. However, although the post-annealing process can accelerate forward aging, on the one hand, the post-annealing will have a negative impact on other functional layers of the light-emitting device, affecting the performance of the light-emitting device to a certain extent. On the other hand, the thickness of the transition oxide interface layer formed by the post-annealing treatment is uncontrollable, and the degree of forward aging cannot be flexibly and accurately controlled.

[0049] The technical solution of this application is as follows:

[0050] First, see Figures 1 to 4 The present invention provides a method for preparing a light-emitting device, comprising the following steps:

[0051] Step S11, providing a light-emitting device preform 200, wherein the light-emitting device preform 200 comprises an anode 10, a light-emitting layer 20, and an electronic functional preform layer 101 which are stacked in sequence, wherein the electronic functional preform layer 101 comprises inorganic semiconductor particles;

[0052] Step S12, preparing a conductive layer 102 on the electronic functional prefabricated layer 101, wherein the conductive layer 102 contains metal elements;

[0053] Step S13, irradiating the conductive layer 102 with oxygen ions, so that the region of the electronic functional prefabricated layer 101 close to the conductive layer 102 and the conductive layer 102 together form a transition layer 40, and the region of the electronic functional prefabricated layer 101 not injected with high-energy oxygen ions is the electronic functional layer 30, thereby obtaining a stacked electronic functional layer 30 and a transition layer 40;

[0054] Step S14: preparing a cathode 50 on the transition layer 40 to obtain a light-emitting device 100.

[0055] In the preparation method, when the conductive layer 102 is irradiated with oxygen ions, on the one hand, high-energy oxygen ions are injected into the interface between the conductive layer 102 and the electronic functional prefabricated layer 101 through the conductive layer 102, and the high-energy oxygen ions injected into the interface can react with the inorganic semiconductor particles and the metal elements at the interface to obtain M'O x and M” n O y , wherein M' and M" are metal elements, x is any value from 0.1 to 1, y is any value from 0.1 to 1, n is any value from 1 to 5, and M'O x and M” n O y A mixed state is formed, so that the area of ​​the electronic functional prefabricated layer 101 close to the conductive layer 102 and the conductive layer 102 together form a transition layer 40; on the other hand, the oxygen ion irradiation can also provide energy to change the lattice structure of the material irradiated by oxygen ions to form the transition layer 40.

[0056] The transition layer 40 includes M'O x and M” n O y In the transition layer 40, along the side close to the electronic functional layer 30 toward the side away from the electronic functional layer 30, M'O x The value of x gradually increases, and M'O xIn other words, in the transition layer 40, the M'O on the side close to the electronic functional layer 30 is x The content of M'O is higher than that of M'O on the side away from the electronic functional layer 30. x In the transition layer 40, along the side close to the cathode 50 toward the side away from the cathode 50, the M" n O y The value of y in the equation decreases gradually, and M" n O y The content of M is distributed in a gradually decreasing gradient. In other words, in the transition layer 40, the M" on the side close to the cathode 50 is n O y The content of M is higher than that of M" on the side away from the cathode 50 n O y The content.

[0057] In some embodiments, M' is selected from one or more of Zn, Ti, Sn, Zr, Ta, Al, Mg, Li, Mn, Y, La, Cu, Ni, Ce, In, and Ga.

[0058] In some embodiments, the M" is selected from one or more of Ag, Al, Ni, Pt, Au, Ir, Cu, Mo, Ca, Mg, Ba, Sn, and Mg.

[0059] As an example, in at least some embodiments, the M'O x ZnO x 、TiO x SnO x 、ZrO x 、Al2O x MgO x etc., the M" n O y Ag2O y 、Al2O y 、NiO y 、CaO y MgO y ,BaO y SnO y MgO y wait.

[0060] It should be noted that, in the transition layer 40, the M' and the M" may be the same or different.

[0061] In at least some embodiments, x is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.8, or 1.

[0062] In at least some embodiments, y is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.8, or 1.

[0063] In at least some embodiments, n is 1, 2, 3, 4, or 5.

[0064] It should be noted that ion irradiation treatment is a technology that uses high-energy ions to modify materials. Its basic principle is: when high-energy ions pass through the target material, Coulomb electromagnetic interaction is generated between the high-energy ions and the individual atoms in the target material. In the process of interaction between the high-energy ions and the target material, due to the loss of electron energy and nuclear energy of the high-energy ions, the high-energy ions will gradually slow down and eventually stay in the crystal lattice of the target material, causing changes such as distortion of the lattice or penetrating the target material, thereby causing changes in the physical, chemical or electrical properties of the target material, thereby changing the physical, chemical or electrical properties of the target material.

[0065] The method for preparing the light-emitting device described in the present application comprises first forming a conductive layer 102 containing metal elements on the electronic functional prefabricated layer 101, and then irradiating the conductive layer 102 with oxygen ions, so that high-energy oxygen ions pass through the conductive layer 102 and are injected into the interface between the conductive layer 102 and the electronic functional prefabricated layer 101. The high-energy oxygen ions injected into the interface can react with the inorganic semiconductor particles and the metal elements at the interface to obtain M'O x and M” n O y , wherein M' and M" are metal elements, x is any value from 0.1 to 1, y is any value from 0.1 to 1, n is any value from 1 to 4, and M'O x and M” n O y A mixed state is formed, so that the region of the electronic functional prefabricated layer 101 close to the conductive layer 102 and the conductive layer 102 together form a transition layer 40, which is beneficial to the forward aging of the device. The transition layer 40 can effectively reduce the contact barrier between the cathode 50 and the electronic functional layer, thereby improving the maximum brightness and life of the light-emitting device 100.

[0066] The present application forms a conductive layer 102 containing metal elements on the electronic functional prefabricated layer 101 first. The conductive layer 102 is equivalent to the area of ​​the cathode of the unaged light-emitting device close to the electronic functional layer. The conductive layer 102 is irradiated with oxygen ions to simulate the forward aging of the electronic functional layer and the cathode of the light-emitting device, which is beneficial to improving the performance of the device such as the maximum brightness and life span.

[0067] In addition, by using oxygen ion irradiation to promote forward aging, on the one hand, the thickness of the transition layer 40 can be controlled by controlling the parameters of oxygen ion irradiation, and the degree of forward aging can be effectively controlled; on the other hand, by using high-energy oxygen ions to promote forward aging, the oxygen required for chemical reactions can be supplemented, thereby reducing the formation of surface defects of inorganic semiconductor particles, and further improving the maximum brightness and life of the light-emitting device 100 and other performance.

[0068] In some embodiments, the energy of the ion beam of the oxygen ion irradiation is 15-50 keV, for example, 15 keV, 20 keV, 25 keV, 30 keV, 35 keV, 40 keV, 45 keV, 50 keV, 55 keV, etc. Within the energy range, high-energy oxygen ions can be effectively promoted to react with inorganic semiconductor particles and metal elements at the interface between the conductive layer 102 and the electronic functional prefabricated layer 101, thereby effectively promoting forward aging and forming a transition layer 40 with a suitable thickness.

[0069] In some embodiments, the oxygen ion dose used in the oxygen ion irradiation is 1×10 12 ~1×10 16 ions / cm 2 , for example, 1×10 12 ions / cm 2 , 2×10 12 ions / cm 2 , 5×10 12 ions / cm 2 , 8×10 12 ions / cm 2 , 1×10 13 ions / cm 2 , 2×10 13 ions / cm 2 , 5×10 13 ions / cm 2 , 8×10 13 ions / cm 2 , 1×10 14 ions / cm 2 , 2×10 14 ions / cm 2 , 5×10 14 ions / cm 2 , 8×10 14 ions / cm 2 , 1×10 15 ions / cm 2 , 2×10 15 ions / cm 2 , 5×1015 ions / cm 2 , 8×10 15 ions / cm 2 ,9×10 15 ions / cm 2 , 1×10 16 ions / cm 2 In the dosage range of oxygen ions, high-energy oxygen ions can be effectively promoted to react with inorganic semiconductor particles and metal elements at the interface between the conductive layer 102 and the electronic functional prefabricated layer 101, thereby effectively promoting forward aging and forming a transition layer 40 with a suitable thickness.

[0070] In some embodiments, the instrument used for the ion irradiation treatment is a known instrument for ion irradiation treatment, such as an ion implanter, an ion accelerator, and the like.

[0071] The average thickness of the conductive layer 102 is 5-30 nm, for example, 5 nm, 8 nm, 10 nm, 15 nm, 18 nm, 20 nm, 22 nm, 25 nm, 26 nm, 28 nm, 30 nm, etc. Within the thickness range, it is favorable for oxygen ions to pass through the conductive layer 102 and be injected into the surface of the electronic functional prefabricated layer 101 .

[0072] The average thickness of the transition layer 40 is 10-50 nm, for example, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 36 nm, 38 nm, 40 nm, 45 nm, 50 nm, etc. The average thickness of the transition layer 40 is preferably 20-45 nm, for example, 25 nm, 30 nm, 35 nm, 36 nm, 38 nm, 40 nm, etc. Within the thickness range, the transition layer has good stability.

[0073] The cathode 50 has an average thickness of 50 to 80 nm, for example, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, etc.

[0074] It can be understood that the electronic functional layer 30 can be an electron injection layer or an electron transport layer.

[0075] The material of the conductive layer 102 may include, but is not limited to, one or more of a first metal element, a first alloy, and a first doped metal oxide. The first metal element may include, but is not limited to, any one of Ag, Al, Ni, Pt, Au, Ir, Cu, Mo, Ca, Mg, and Ba. The first alloy may include, but is not limited to, a silver-copper alloy, a silver-nickel alloy, a silver-magnesium alloy, a silver-aluminum alloy, an aluminum-magnesium alloy, an aluminum-magnesium-zinc-copper alloy, or a gold-magnesium alloy. The first doped metal oxide may include, but is not limited to, one or more of indium-doped tin oxide (ITO), fluorine-doped tin oxide (FTO), antimony-doped tin oxide (ATO), aluminum-doped zinc oxide (AZO), gallium-doped zinc oxide (GZO), indium-doped zinc oxide (IZO), magnesium-doped zinc oxide (MZO), aluminum-doped magnesium oxide (AMO), and cadmium-doped zinc oxide.

[0076] It can be understood that when the material of the conductive layer 102 is doped metal oxide, the doping elements thereof can also form metal oxide under the action of high-energy oxygen ions.

[0077] The material of the cathode 50 is a material known in the art for cathodes, for example, it may include but is not limited to one or more of a second metal element, a second alloy, and a second doped metal oxide. The second metal element may include but is not limited to any one of Ag, Al, Ni, Pt, Au, Ir, Cu, Mo, Ca, Mg, and Ba. The second alloy includes but is not limited to silver-copper alloy, silver-nickel alloy, silver-magnesium alloy, silver-aluminum alloy, aluminum-magnesium alloy, aluminum-magnesium-zinc-copper alloy, or gold-magnesium alloy. The second doped metal oxide may include but is not limited to one or more of indium-doped tin oxide (ITO), fluorine-doped tin oxide (FTO), antimony-doped tin oxide (ATO), aluminum-doped zinc oxide (AZO), gallium-doped zinc oxide (GZO), indium-doped zinc oxide (IZO), magnesium-doped zinc oxide (MZO), aluminum-doped magnesium oxide (AMO), and cadmium-doped zinc oxide.

[0078] It can be understood that the materials of the conductive layer 102 and the cathode 50 can be the same or different.

[0079] Please refer to the figure Figure 5 In some embodiments, the light-emitting device preform further includes a hole transport layer 60 , and the hole transport layer 60 is located between the anode 10 and the light-emitting layer 20 .

[0080] In some embodiments, the light emitting device preform further includes a hole injection layer 70 , and the hole injection layer 70 is located between the anode 10 and the hole transport layer 60 .

[0081] The inorganic semiconductor particles are N-type inorganic semiconductor particles known for use in the electronic functional layer of a light-emitting device, and may include, for example, but are not limited to, doped metal oxide particles, undoped metal oxide particles, one or more of Group IIB-VIA semiconductor materials, Group IIIA-VA semiconductor materials, and Group IB-IIIA-VIA semiconductor materials. The material of the undoped metal oxide particles includes, but is not limited to, one or more of ZnO, TiO2, SnO2, ZrO2, and Ta2O5. The metal oxide in the doped metal oxide particles includes, but is not limited to, one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5, and Al2O3. The doping elements in the doped metal oxide particles include, but are not limited to, one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, and Ga. The Group IIB-VIA semiconductor materials include, but are not limited to, one or more of ZnS, ZnSe, and CdS. The Group IIIA-VA semiconductor materials include, but are not limited to, one or more of InP. The Group IB-IIIA-VIA semiconductor materials include, but are not limited to, one or more of CuInS and CuGaS.

[0082] In some embodiments, the average particle size of the inorganic semiconductor particles is 3 to 6 nm.

[0083] The anode 10 is an anode for a light-emitting device known in the art, for example, it may include but is not limited to a doped metal oxide electrode, a composite electrode, a graphene electrode, a carbon nanotube electrode, a metal single substance electrode or an alloy electrode. The material of the doped metal oxide electrode may include but is not limited to one or more of indium doped tin oxide (ITO), fluorine doped tin oxide (FTO), antimony doped tin oxide (ATO), aluminum doped zinc oxide (AZO), gallium doped zinc oxide (GZO), indium doped zinc oxide (IZO), magnesium doped zinc oxide (MZO), aluminum doped magnesium oxide (AMO), and cadmium doped zinc oxide. The composite electrode is an electrode formed by stacking two or more layers of conductive materials, such as AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, Ca / Al, LiF / Ca, LiF / Al, BaF2 / Al, CsF / Al, CaCO3 / Al, BaF2 / Ca / Al, etc., wherein " / " represents a stacked structure, for example, AZO / Ag / AZO represents a composite electrode including a sequentially stacked AZO layer, an Ag layer and an AZO layer. The material of the metal single substance electrode may include but is not limited to one or more of Ag, Ni, Pt, Au, Ir, Cu, Mo, Al, Ca, Mg and Ba. The alloy electrode includes but is not limited to a silver-copper alloy electrode, a silver-nickel alloy electrode, a silver-magnesium alloy electrode, a silver-aluminum alloy electrode, an aluminum-magnesium alloy electrode, an aluminum-magnesium-zinc-copper alloy electrode or a gold-magnesium alloy electrode.

[0084] The material of the light-emitting layer 20 may include, but is not limited to, one or more of an organic light-emitting material and a quantum dot light-emitting material.

[0085] The organic light-emitting material may include, but is not limited to, one or more of CBP:Ir(mppy)3(4,4'-bis(N-carbazole)-1,1'-biphenyl:tri[2-(p-tolyl)pyridine iridium(III)), TCTX:Ir(mmpy)(4,4',4"-tri(carbazole-9-yl)triphenylamine:tri[2-(p-tolyl)pyridine iridium), diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, TADF (thermally activated delay) materials, polymers containing covalent bonds of BN, HLCT (hybridized localized charge transfer excited state) materials, Exciplex (exciplex) light-emitting materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives.

[0086] The quantum dot light-emitting material may include, but is not limited to, one or more of single structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials.

[0087] The material of the single structure quantum dots, the core material of the core-shell structure quantum dots and the shell material of the core-shell structure quantum dots may respectively include but are not limited to one or more of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds. The II-VI group compounds may include, but are not limited to, one or more of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe. The IV-VI group compounds may include, but are not limited to, one or more of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe. The III-V group compound may include, but is not limited to, one or more of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, and InAlPSb. The I-III-VI group compound may include, but is not limited to, one or more of CuInS2, CuInSe2, and AgInS2.

[0088] As an example, the core-shell structured quantum dots may include, but are not limited to, one or more of CdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZnSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / ZnS, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS and InP / ZnSe / ZnS.

[0089] The perovskite semiconductor material may include but is not limited to doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors. The inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ions, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion, including Cl - Br - ,I - The general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation, including CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion, including Cl - Br - ,I - One or more of .

[0090] The material of the hole transport layer 60 can be a material known in the art for a hole transport layer, for example, can be selected from but not limited to 4,4'-N,N'-dicarbazolyl-biphenyl (CBP), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine (α-NPD), N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine (TPD), poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine) (Poly-TPD), N ...1-naphthyl)-1,1'-biphenyl-4,4"-diamine (α-NPD), N (3-methylphenyl)-N,N'-bis(phenyl)-spiro(spiro-TPD), N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine (DNTPD), 4,4',4'-tri(N-carbazolyl)-triphenylamine (TCTA), 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine (m-MTDATA), poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))] (TFB), poly(N-vinylcarbazole) (PVK) and its derivatives, N,N'-di(1-naphthyl)-N,N'-diphenyl -1,1'-biphenyl-4-4'-diamine (NPB), spiro NPB, poly(phenylene vinylene) (PPV), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] (MEH-PPV), poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene] (MOMO-PPV), 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-omeTAD), 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline] (TAPC), 1,3-bis(carbazol-9-yl)benzene (MCP ), polyaniline, polypyrrole, poly(p-)phenylene vinylene, aromatic tertiary amine, polynuclear aromatic tertiary amine, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compound, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, doped graphene, undoped graphene, C60, doped or undoped NiO, doped or undoped MoO3, doped or undoped WO3, doped or undoped V2O5, doped or undoped P-type gallium nitride, doped or undoped CrO3, doped or undoped CuO. One or more.

[0091] The material of the hole injection layer 70 can also be a material known in the art for hole injection layer, for example, it can be selected from but not limited to 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene (HAT-CN), PEDOT, PEDOT:PSS, PEDOT:PSS doped with s-MoO3 derivatives (PEDOT:PSS:s-MoO3), 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine (m-MTDATA), tetracyanoquinodimethane (F4-TCQN), copper phthalocyanine, nickel oxide, molybdenum oxide, tungsten oxide, vanadium oxide, molybdenum sulfide, tungsten sulfide and copper oxide. One or more.

[0092] The methods for preparing the electronic functional prefabricated layer 101, the conductive layer 102, and the cathode 50 described in the present application can be implemented by conventional techniques in the art, such as chemical methods or physical methods. Among them, the chemical method includes chemical vapor deposition, continuous ion layer adsorption and reaction, anodization, electrolytic deposition, and coprecipitation. The physical method includes physical plating and solution method, among which the physical plating method includes: thermal evaporation coating, electron beam evaporation coating, magnetron sputtering, multi-arc ion plating, physical vapor deposition, atomic layer deposition, pulsed laser deposition, etc.; the solution method can be spin coating, printing, inkjet printing, blade coating, printing, dip-pull method, immersion method, spraying, roll coating, casting, slit coating, and strip coating, etc.

[0093] It can be understood that when the light-emitting device 100 also includes functional layers conventionally used in light-emitting devices that help improve the performance of the light-emitting device, such as an electron blocking layer, a hole blocking layer, an interface modification layer, etc., the preparation method of the light-emitting device 100 may also include the step of preparing the above-mentioned functional layers using conventional techniques in the field.

[0094] It can be understood that the materials of each layer of the light emitting device 100 can be adjusted according to the light emitting requirements of the light emitting device 100 .

[0095] In some embodiments, the light-emitting device preform further includes a substrate, and the substrate is located on a side of the anode 10 away from the light-emitting layer 20 .

[0096] The substrate may be a rigid substrate or a flexible substrate. In some embodiments, the material of the substrate may include but is not limited to one or more of glass, silicon wafer, polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene naphthalate, polyamide and polyether sulfone.

[0097] It can be understood that the light emitting device 100 can be a positive light emitting device or an inverted light emitting device. The light emitting device 100 can be a quantum dot light emitting device or an organic light emitting device.

[0098] Second, see Figure 4 The present application also provides a light emitting device 100 prepared by the above-mentioned method for preparing a light emitting device. The light emitting device 100 includes an anode 10, a light emitting layer 20, an electronic functional layer 30, a transition layer 40 and a cathode 50 which are stacked in sequence. The transition layer 40 includes M'O x and M” n O y , wherein M' and M" are metal elements, x is any value from 0.1 to 1, y is any value from 0.1 to 1, and n is any value from 1 to 5.

[0099] In some embodiments, M' is selected from one or more of Zn, Ti, Sn, Zr, Ta, Al, Mg, Li, Mn, Y, La, Cu, Ni, Ce, In, and Ga.

[0100] In some embodiments, the M" is selected from one or more of Ag, Al, Ni, Pt, Au, Ir, Cu, Mo, Ca, Mg, Ba, Sn, and Mg.

[0101] As an example, in at least some embodiments, the M'O x ZnO x 、TiO x SnO x 、ZrO x 、Al2O x MgO x , CuO x 、NiO x 、Mn2O x etc., the M" n O y Ag2O y 、Al2O y 、NiO y , CuO y 、CaO y MgO y ,BaO y SnO y MgO y wait.

[0102] It should be noted that, in the transition layer 40, the M' and the M" may be the same or different.

[0103] In at least some embodiments, x is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.8, or 1.

[0104] In at least some embodiments, y is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.8, or 1.

[0105] In at least some embodiments, n is 1, 2, 3, 4, or 5.

[0106] In some embodiments, in the transition layer 40, along the side close to the electronic functional layer 30 toward the side away from the electronic functional layer 30, M′O x The value of x gradually increases, and M'O x In other words, in the transition layer 40, the M'O on the side close to the electronic functional layer 30 is x The content of M'O is higher than that of M'O on the side away from the electronic functional layer 30. x In the transition layer 40, along the side close to the cathode 50 toward the side away from the cathode 50, the M" n O y The value of y in the equation decreases gradually, and M" n O y The content of M is distributed in a gradually decreasing gradient. In other words, in the transition layer 40, the M" on the side close to the cathode 50 is n O y The content of M is higher than that of M" on the side away from the cathode 50 n O y The content.

[0107] The average thickness of the transition layer 40 is in the range of 10 to 50 nm, for example, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 36 nm, 38 nm, 40 nm, 45 nm, 50 nm, etc., preferably, 20 to 45 nm, for example, 25 nm, 30 nm, 35 nm, 36 nm, 38 nm, 40 nm, etc.

[0108] See also Figure 5 In some embodiments, the light-emitting device 100 further includes a hole transport layer 60 located between the anode 10 and the light-emitting layer 20 .

[0109] In some embodiments, the light emitting device 100 further includes a hole injection layer 70 located between the anode 10 and the hole transport layer 60 .

[0110] In a third aspect, the present application further relates to a display device, which includes the light-emitting device 100 .

[0111] The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptops, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, among which smart wearable devices can be, for example, smart bracelets, smart watches, virtual reality (VR) helmets, etc.

[0112] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.

[0113] Example 1

[0114] Providing a substrate having an ITO anode 10 with a thickness of 80 nm, ultrasonically cleaning the ITO-coated substrate with acetone and ethanol for 15 minutes, then cleaning it again with deionized water, then drying it on a hot plate at 150° C. for 10 minutes, and finally irradiating it with ultraviolet light for 20 minutes to improve the work function and surface energy of ITO;

[0115] In a glove box, a PEDOT:PSS material with a mass concentration of 2.8% was spin-coated on the anode 10 at a spin-coating speed of 3000 rpm for 30 seconds, and annealed at 150° C. for 20 minutes to obtain a hole injection layer 70 with a thickness of 20 nm;

[0116] Spin coating the TFB material with a concentration of 6.5 mg / mL on the hole injection layer 70 at a spin coating speed of 3000 rpm for 30 seconds, and annealing at 120° C. for 20 minutes to obtain a hole transport layer 60 with a thickness of 20 nm;

[0117] Spin-coat CdZnSe blue light quantum dots with a concentration of 10 mg / mL on the hole transport layer 60 at a spin-coating speed of 1500 rpm for 30 seconds and anneal at 100° C. for 5 minutes to obtain a light-emitting layer 20 with a thickness of 40 nm;

[0118] Spin-coat a 30 mg / mL ZnO ethanol solution on the light-emitting layer 20 at a spin-coating speed of 4000 rpm for 30 seconds, and anneal at 80° C. for 10 minutes to obtain an electronic functional prefabricated layer 101 with a thickness of 65 nm;

[0119] Ag material is evaporated on the electronic functional prefabricated layer 101 at a rate of 1 angstrom / second for 20 seconds, wherein the vacuum degree is not higher than 3×10 -4 Pa, to obtain a conductive layer 102 with a thickness of 20 nm;

[0120] In an ion implanter, the conductive layer 102 is irradiated with oxygen ions, wherein the energy of the oxygen ion beam generated by the ion implanter is 35 keV, and the dose of the oxygen ions is 1×10 14 ions / cm 2 , forming an electron transport layer with an average thickness of 35 nm combined with the light-emitting layer 20 and a transition layer 40 with an average thickness of 30 nm combined with the surface of the electron transport layer away from the light-emitting layer 20;

[0121] Ag material was evaporated on the transition layer 40 at a rate of 1 angstrom / second for 80 seconds, wherein the vacuum degree was not higher than 3×10 - 4 Pa, and a cathode 50 having a thickness of 80 nm is obtained;

[0122] Packaging to obtain a light-emitting device.

[0123] Example 2

[0124] This embodiment is basically the same as embodiment 1, except that in this embodiment, the dosage of oxygen ions is 1×10 12 ions / cm 2 The average thickness of the transition layer 40 is 40 nm, and the average thickness of the electron transport layer is 25 nm.

[0125] Example 3

[0126] This embodiment is basically the same as embodiment 1, except that in this embodiment, the dosage of oxygen ions is 1×10 16 ions / cm 2 The average thickness of the transition layer 40 is 40 nm, and the average thickness of the electron transport layer is 25 nm.

[0127] Example 4

[0128] This embodiment is basically the same as Embodiment 1, except that, in this embodiment, Al is used to replace Ag in Embodiment 1 when preparing the cathode 50, the average thickness of the transition layer 40 is 40 nm, and the average thickness of the electron transport layer is 25 nm.

[0129] Example 5

[0130] This embodiment is basically the same as Embodiment 1, except that, in this embodiment, Al is used to replace Ag in Embodiment 1 when preparing the conductive layer 102, Al is used to replace Ag in Embodiment 1 when preparing the cathode 50, the average thickness of the transition layer 40 is 35 nm, and the average thickness of the electron transport layer is 30 nm.

[0131] Example 6

[0132] This embodiment is substantially the same as Embodiment 1, except that, in this embodiment, the energy of the oxygen ion beam is 15 keV, the average thickness of the transition layer 40 is 25 nm, and the average thickness of the electron transport layer is 40 nm.

[0133] Example 7

[0134] This embodiment is substantially the same as Embodiment 1, except that, in this embodiment, the energy of the oxygen ion beam is 55 keV, the average thickness of the transition layer 40 is 38 nm, and the average thickness of the electron transport layer is 27 nm.

[0135] Example 8

[0136] This embodiment is basically the same as Embodiment 1, except that, in this embodiment, Al-Ag alloy (silver-aluminum alloy) is used to replace Ag in Embodiment 1 when preparing the conductive layer 102, the average thickness of the transition layer 40 is 35 nm, and the average thickness of the electron transport layer is 30 nm.

[0137] Example 9

[0138] This embodiment is basically the same as Embodiment 1, except that, in this embodiment, aluminum-doped zinc oxide (AZO) is used to replace Ag in Embodiment 1 when preparing the conductive layer 102, the average thickness of the transition layer 40 is 36 nm, and the average thickness of the electron transport layer is 29 nm.

[0139] Example 10

[0140] This embodiment is basically the same as Embodiment 1, except that, in this embodiment, Al-Ag alloy is used to replace Ag in Embodiment 1 when preparing cathode 50, the average thickness of transition layer 40 is 30 nm, and the average thickness of electron transport layer is 35 nm.

[0141] Embodiment 11

[0142] This embodiment is basically the same as Embodiment 1, except that, in this embodiment, Mg-doped ZnO is used to replace ZnO in Embodiment 1.

[0143] Example 12

[0144] This embodiment is basically the same as Embodiment 1, except that, in this embodiment, SnO2 is used to replace ZnO in Embodiment 1.

[0145] Comparative Example 1

[0146] This comparative example is basically the same as Example 1, except that in this comparative example, the preparation method of the cathode 50 is:

[0147] Ag material was evaporated on the electron transport layer at a rate of 1 angstrom / second for 100 seconds, wherein the vacuum degree was not higher than 3×10 -4 Pa, and a cathode with a thickness of 100 nm was obtained.

[0148] Comparative Example 2

[0149] This comparative example is substantially the same as Example 5, except that in this comparative example, the preparation method of the cathode 50 is:

[0150] Al material is evaporated on the electron transport layer at a rate of 1 angstrom / second for 100 seconds, wherein the vacuum degree is not higher than 3×10 -4 Pa, and a cathode with a thickness of 100 nm was obtained.

[0151] Comparative Example 3

[0152] This comparative example is substantially the same as Example 8, except that in this comparative example, the preparation method of the cathode 50 is:

[0153] Al-Ag alloy material is evaporated on the electron transport layer at a rate of 1 angstrom / second for 100 seconds, wherein the vacuum degree is not higher than 3×10 -4 Pa, and a cathode with a thickness of 100 nm was obtained.

[0154] Comparative Example 4

[0155] This comparative example is substantially the same as Example 9, except that in this comparative example, the preparation method of the cathode 50 is:

[0156] Aluminum-doped zinc oxide (AZO) is evaporated on the electron transport layer at a rate of 1 angstrom / second for 100 seconds, wherein the vacuum degree is not higher than 3×10 -4 Pa, and a cathode with a thickness of 100 nm was obtained.

[0157] Comparative Example 5

[0158] This comparative example is substantially the same as Example 11, except that in this comparative example, the preparation method of the cathode 50 is:

[0159] Ag material was evaporated on the electron transport layer at a rate of 1 angstrom / second for 100 seconds, wherein the vacuum degree was not higher than 3×10 -4 Pa, and a cathode with a thickness of 100 nm was obtained.

[0160] Comparative Example 6

[0161] This comparative example is substantially the same as Example 12, except that in this comparative example, the preparation method of the cathode 50 is:

[0162] Ag material was evaporated on the electron transport layer at a rate of 1 angstrom / second for 100 seconds, wherein the vacuum degree was not higher than 3×10 -4 Pa, and a cathode with a thickness of 100 nm was obtained.

[0163] Light-emitting device performance testing:

[0164] The light emitting devices of Examples 1, 5, 8, 9, 11, 12 and Comparative Examples 1 to 6 were subjected to JVL data testing. Figures 6-7 ,in, Figure 6 is a voltage-current density curve of the light emitting devices of Examples 1, 5, 8, 9, 11, 12 and Comparative Examples 1 to 6, Figure 7 It is a current density-external quantum efficiency curve of the light-emitting devices of Examples 1, 5, 8, 9, 11, 12 and Comparative Examples 1 to 6.

[0165] Depend on Figure 6 It can be seen that under the same voltage, the current density of the light-emitting device of Example 1 is higher than that of the light-emitting device of Comparative Example 1. Figure 7 It can be seen that at the same current density, the external quantum efficiency of the light-emitting device of Example 1 is higher than that of the light-emitting device of Comparative Example 1. That is to say, at the same voltage, the external quantum efficiency of the light-emitting device of Example 1 is higher than that of the light-emitting device of Comparative Example 1. It can be seen that the light-emitting device prepared by the preparation method of the present application can have a higher luminous efficiency.

[0166] Depend on Figure 6 It can be seen that under the same voltage, the current density of the light-emitting device of Example 2 is higher than that of the light-emitting device of Comparative Example 2. Figure 7 It can be seen that, at the same current density, the external quantum efficiency of the light-emitting device of Example 2 is higher than that of the light-emitting device of Comparative Example 2. That is to say, at the same voltage, the external quantum efficiency of the light-emitting device of Example 2 is higher than that of the light-emitting device of Comparative Example 2. It can be seen that the light-emitting device prepared by the preparation method of the present application can have a higher luminous efficiency.

[0167] Depend on Figure 6 It can be seen that under the same voltage, the current density of the light-emitting device of Example 3 is higher than that of the light-emitting device of Comparative Example 3. Figure 7 It can be seen that, at the same current density, the external quantum efficiency of the light-emitting device of Example 3 is higher than that of the light-emitting device of Comparative Example 3. That is to say, at the same voltage, the external quantum efficiency of the light-emitting device of Example 3 is higher than that of the light-emitting device of Comparative Example 3. It can be seen that the light-emitting device prepared by the preparation method of the present application can have a higher luminous efficiency.

[0168] Depend on Figure 6 It can be seen that under the same voltage, the current density of the light-emitting device of Example 4 is higher than that of the light-emitting device of Comparative Example 4. Figure 7 It can be seen that, at the same current density, the external quantum efficiency of the light-emitting device of Example 4 is higher than that of the light-emitting device of Comparative Example 4. That is to say, at the same voltage, the external quantum efficiency of the light-emitting device of Example 4 is higher than that of the light-emitting device of Comparative Example 4. It can be seen that the light-emitting device prepared by the preparation method of the present application can have a higher luminous efficiency.

[0169] Depend on Figure 6 It can be seen that under the same voltage, the current density of the light-emitting device of Example 5 is higher than that of the light-emitting device of Comparative Example 5. Figure 7 It can be seen that, at the same current density, the external quantum efficiency of the light-emitting device of Example 5 is higher than that of the light-emitting device of Comparative Example 5. That is to say, at the same voltage, the external quantum efficiency of the light-emitting device of Example 5 is higher than that of the light-emitting device of Comparative Example 5. It can be seen that the light-emitting device prepared by the preparation method of the present application can have a higher luminous efficiency.

[0170] Depend on Figure 6 It can be seen that under the same voltage, the current density of the light-emitting device of Example 6 is higher than that of the light-emitting device of Comparative Example 6. Figure 7 It can be seen that, at the same current density, the external quantum efficiency of the light-emitting device of Example 6 is higher than that of the light-emitting device of Comparative Example 6. That is to say, at the same voltage, the external quantum efficiency of the light-emitting device of Example 6 is higher than that of the light-emitting device of Comparative Example 6. It can be seen that the light-emitting device prepared by the preparation method of the present application can have a higher luminous efficiency.

[0171] The maximum brightness L of the light emitting devices of Examples 1 to 12 and Comparative Examples 1 to 6 is max , lifespan T95, and lifespan T95@1000nit were tested. The test results are shown in Table 1.

[0172] Among them, the maximum brightness L max The test method is: using FSD FPD optical property measurement equipment, controlling the efficiency test system built by QE PRO spectrometer, Keithley 2400, and Keithley 6485 through LabView, measuring parameters such as voltage, current, brightness, and luminous spectrum, and calculating the current efficiency;

[0173] The test method for life span T95 and life span T95@1000nit is: in CDA gas, under constant current drive, measure the time taken for the device brightness to decay to a certain proportion of the maximum brightness, and the time taken for the brightness to decay to 95% of the maximum brightness is defined as T95, and the life span is the measured life span. In order to shorten the life span test cycle, the device life span test is usually carried out at high brightness by accelerating device aging, and the life span at low brightness is obtained by fitting the decay fitting formula. For example, the life span at 1000nits is recorded as T95@1000nits, and the calculation formula is:

[0174]

[0175] Among them, T95 L The lifespan under low brightness, generally 1000nits, T95 H is the lifespan under high brightness, that is, the measured lifespan, L H is the maximum brightness that the device is accelerated to, L L Generally, it is 1000nits, A is the acceleration factor, which is 1.7. The constant current is 1mA.

[0176] Table 1:

[0177]

[0178]

[0179] From Table 1 we can see that:

[0180] Compared with the light-emitting devices of comparative examples 1 to 6, the light-emitting devices of embodiments 1 to 12 have higher maximum brightness and longer lifespan. It can be seen that the preparation method of the present application can improve the maximum brightness and lifespan of the light-emitting devices. The reason is that oxygen ion irradiation forms a transition layer, which promotes the aging of the device.

[0181] The above describes in detail the preparation method of the light-emitting device, the light-emitting device and the display device provided in the embodiments of the present application. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A method for preparing a light-emitting device, characterized in that: The steps include: Providing a light-emitting device prefabricated part, the light-emitting device prefabricated part comprising an anode, a light-emitting layer, and an electronic functional prefabricated layer stacked in sequence, wherein the electronic functional prefabricated layer comprises inorganic semiconductor particles; Preparing a conductive layer on the electronic functional prefabricated layer, wherein the conductive layer contains a metal element; The conductive layer is subjected to oxygen ion irradiation, so that the region of the electronic functional prefabricated layer close to the conductive layer and the conductive layer form a transition layer together, thereby obtaining a laminated electronic functional layer and a transition layer; A cathode is prepared on the transition layer to obtain a light-emitting device.

2. The preparation method according to claim 1, characterized in that The energy of the ion beam of the oxygen ion irradiation is 15 to 50 keV; and / or The oxygen ion dose used in the oxygen ion irradiation is 1×10 12 ~1×10 16 ions / cm 2 .

3. The preparation method according to claim 1, characterized in that: The average thickness of the conductive layer is 5 to 30 nm; and / or The average thickness of the transition layer is in the range of 10 to 50 nm.

4. The preparation method according to claim 1, characterized in that: The material of the conductive layer includes one or more of a metal element, a metal alloy and a doped metal oxide; wherein the metal element includes Ag, Al, Ni, Pt, Au, Ir, Cu, Mo, Ca, Mg and Ba; the metal alloy is composed of at least two metal elements in the metal element; optionally, the metal alloy includes a silver-copper alloy, a silver-nickel alloy, a silver-magnesium alloy, a silver-aluminum alloy, an aluminum-magnesium alloy, an aluminum-magnesium-zinc-copper alloy or a gold-magnesium alloy; the doped metal oxide includes one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide, aluminum-doped magnesium oxide and cadmium-doped zinc oxide; and / or The inorganic semiconductor particles include doped metal oxide particles, undoped metal oxide particles, one or more of IIB-VIA semiconductor materials, IIIA-VA semiconductor materials and IB-IIIA-VIA semiconductor materials. The material of the undoped metal oxide particles includes one or more of ZnO, TiO2, SnO2, ZrO2, and Ta2O5. The metal oxide in the doped metal oxide particles includes one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5, and Al2O3. The doping elements in the doped metal oxide particles include one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, and Ga. The IIB-VIA semiconductor materials include one or more of ZnS, ZnSe, and CdS. The IIIA-VA semiconductor materials include one or more of InP. The IB-IIIA-VIA semiconductor materials include one or more of CuInS and CuGaS.

5. The preparation method according to claim 1, characterized in that: The anode includes a doped metal oxide electrode, a composite electrode, a graphene electrode, a carbon nanotube electrode, a metal single substance electrode or an alloy electrode. The material of the doped metal oxide electrode includes one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide, aluminum-doped magnesium oxide, and cadmium-doped zinc oxide. The composite electrode includes AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / A g / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, Ca / Al, LiF / Ca, LiF / Al, BaF2 / Al, CsF / Al, CaCO3 / Al or BaF2 / Ca / Al, the material of the metal single substance electrode includes one or more of Ag, Ni, Pt, Au, Ir, Cu, Mo, Al, Ca, Mg and Ba, and the alloy electrode includes a silver-copper alloy electrode, a silver-nickel alloy electrode, a silver-magnesium alloy electrode, a silver-aluminum alloy electrode, an aluminum-magnesium alloy electrode, an aluminum-magnesium-zinc-copper alloy electrode or a gold-magnesium alloy electrode; and / or The material of the light-emitting layer includes one or more of an organic light-emitting material and a quantum dot light-emitting material, and the organic light-emitting material includes one or more of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tri[2-(p-tolyl)pyridine iridium(III), 4,4',4"-tri(carbazole-9-yl)triphenylamine:tri[2-(p-tolyl)pyridine iridium, diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, thermally activated delayed materials, polymers containing covalent bonds of BN, hybrid localized charge transfer excited state materials, exciplex light-emitting materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives;The quantum dot luminescent material includes one or more of a single structure quantum dot, a core-shell structure quantum dot and a perovskite semiconductor material. The material of the single structure quantum dot, the core material of the core-shell structure quantum dot and the shell material of the core-shell structure quantum dot are independently selected from one or more of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds. The II-VI group compounds include CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, Zn STe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound includes SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, One or more of PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, the III-V group compound includes GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlN As, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, the I-III-VI group compound includes one or more of CuInS2, CuInSe2 and AgInS2; the perovskite semiconductor material includes a doped or undoped inorganic perovskite semiconductor or an organic-inorganic hybrid perovskite semiconductor, and the general structural formula of the inorganic perovskite semiconductor is AMX3, wherein A is Cs; + ions, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion, including Cl - Br - ,I - One or more of; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation, including CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion, including Cl - Br - ,I - One or more of; and / or The light-emitting device further comprises a hole transport layer between the anode and the light-emitting layer, wherein the material of the hole transport layer comprises 4,4'-N,N'-dicarbazolyl-biphenyl, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine), N,N'-bis(3 -methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(N-vinylcarbazole) and its derivatives, N,N'-di(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4- 4'-diamine, spiro NPB, poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene], poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline], 1,3-bis(carbazol-9-yl)benzene, polyaniline, polypyrrole, poly(p-)phenylene vinylene, aromatic tertiary amines, polynuclear aromatic tertiary amines , 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, doped graphene, undoped graphene, C60, doped or undoped NiO, doped or undoped MoO3, doped or undoped WO3, doped or undoped V2O5, doped or undoped P-type gallium nitride, doped or undoped CrO3, doped or undoped CuO; and / or The light-emitting device also includes a hole injection layer located between the anode and the light-emitting layer, and the material of the hole injection layer includes one or more of 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, PEDOT, PEDOT:PSS, a derivative of PEDOT:PSS doped with s-MoO3, 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, tetracyanoquinodimethane, copper phthalocyanine, nickel oxide, molybdenum oxide, tungsten oxide, vanadium oxide, molybdenum sulfide, tungsten sulfide and copper oxide.

6. A light-emitting device, comprising an anode, a light-emitting layer, an electronic functional layer and a cathode stacked in sequence, characterized in that: It also includes a transition layer, the transition layer is located between the electronic functional layer and the cathode, and the transition layer includes M'O x and M” n O y , wherein M' and M" are metal elements, x is any value from 0.1 to 1, y is any value from 0.1 to 1, and n is any value from 1 to 5.

7. The light emitting device according to claim 6, characterized in that: The M' is selected from one or more of Zn, Ti, Sn, Zr, Ta, Al, Mg, Li, Mn, Y, La, Cu, Ni, Ce, In, and Ga; and / or The M" is selected from one or more of Ag, Al, Ni, Pt, Au, Ir, Cu, Mo, Ca, Mg, Ba, Sn, and Mg; Optionally, the M'O x ZnO x , the M" n O y Ag2O y .

8. The light emitting device according to claim 6, characterized in that: In the transition layer, along the side close to the electronic functional layer toward the side away from the electronic functional layer, the M′O x The value of x gradually increases, and M'O x The content of In the transition layer, M'O on the side close to the electronic functional layer x The content of M'O is higher than that of M'O on the side away from the electronic functional layer. x content; and / or In the transition layer, along the side close to the cathode toward the side away from the cathode, the M" n O y The value of y in the equation decreases gradually, and M" n O y The content of In the transition layer, M" on the side close to the cathode n O y The content is higher than that of M" on the side away from the cathode n O y The content.

9. The light emitting device according to claim 6, characterized in that: The average thickness of the transition layer is 10 to 50 nm, preferably 20 to 45 nm.

10. A display device, characterized in that: The display device comprises a light-emitting device manufactured by the manufacturing method according to any one of claims 1 to 5, or comprises a light-emitting device according to any one of claims 6 to 9.